Spatial TEC gradients for geomagnetic storms in March, April and November of 2023 for an Eastern North-Atlantic Midlatitudinal Zone ... - Morozova, Anna; Barata, Teresa (figshare, 2024)
The UQRG (15 min cadence) GIMs were downloaded from CDDIS (The Crustal Dynamics Data Information System, https://cddis.nasa.gov/archive/gnss/products/ionex/). The maps were cropped accordingly to the Eastern North-Atlantic Midlatitudinal Zone (Eastern North-Atlantic Midlatitudinal Zone.jpg) boundaries.A scheme described in ( Liu, Q., Hernández‐Pajares, M., Yang, H., Monte‐Moreno, E., García‐Rigo, A., Lyu, H., Olivares‐Pulido, G. and Orús‐Pérez, R. (2022) A New Way of Estimating the Spatial and Temporal Components of the Vertical Total Electron Content Gradient Based on UPC‐IonSAT Global Ionosphere Maps. Space Weather, 20(2), p.e2021SW002926 ) was used to calculate TEC gradients for each of gridpoints. The animations show TEC gradients evolution during selected days around the following geomagnetic storms: March 23-24, 2023, (Dst_min = -163 nT); April 23-24, (Dst_min = -212 nT); November 4-5, (Dst_min = -172 nT). ...